(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rohman F, Priambodo B, Akhsani F, Rahayu SE, Wangkulang S, Kundariati M. 2022. Revealing herpetofauna diversity at Brantas River, East Java, Indonesia: Evidence of decreasing populations. Biodiversitas 23: 1475-1481. Conservation planning is very important to preserve nature and ecosystems. Based on this, exploration and species inventory in nature need to be carried out. Group of animals that have an important role in the environment is herpetofauna. This study aims to reveal the abundance, evenness, and richness of herpetofauna in Brantas River’s streams connection. This study uses the Visual Encounter Surveys (VES) sampling method at 8 points located in Blitar, Tulungagung, Malang, Mojokerto, Kediri, and Batu City, East Java, Indonesia. The results showed that the diversity index (H’) 1 < 2, 3959 < 3, with the criteria for the diversity index being moderate. The value of e is 0.74 > 0.6, which means high species uniformity. Specific richness has a value of 4.53 which means in the moderate category. There were 12 species of amphibians and 14 reptile species. Five species are of low-risk status with decreasing population in nature and two species is of vulnerable status. Species in the declining category are Odorrana hosii, Limnonectes microdiscus Wijayarana masonii, Leptobrachium hasseltii, and Philautus aurifasciatus. Species in the vulnerable category are Microhyla orientalis and Gonocephalus kuhlii. Species in the declining category require attention from conservation efforts because their presence is important in various aspects of the ecosystem, such as the food chain, bioindicators, and natural enemies.